From responsibility to value: ESG and long-term corporate value - Fang, Lanlin; Guo, Xuemeng (PLOS ONE, 2025)
Although a large body of literature has explored the relationship between ESG and firm value, the findings are inconsistent and most studies have focused on mature Western markets, with relatively little research on ESG practices and value creation effects in emerging markets, especially in transition economies such as China. This paper analyzes the correlation between ESG performance and firms’ long-term value using data from 4,185 listed companies in China’s A-share market from 2017–2022. We find that good ESG practices can significantly enhance firms’ future cash flows, long-term value and market competitiveness. The results suggest that ESG increases long-term firm value by reducing weighted average cost and increasing return on invested capital. The effects of firms’ HHI index, nature of property rights and ISO 9001 system certification on the relationship are further investigated and it is found that Lerner’s index acts as a mediating variable to enable ESG performance to affect firms’ long-term value by enhancing their market pricing power and competitiveness. This paper serves as an important reference for corporate managers to integrate ESG concepts into strategic planning for sustainable development and long-term value growth, helping enterprises implement ESG strategies for long-term corporate success and sustainable development.